Differences in platelet endothelial cell adhesion molecule-1 expression between peripheral circulation and pancreatic microcirculation in cerulein-induced acute edematous pancreatitis - Gao, Hong-Kai (World J Gastroenterol, 2005)
AIM: To investigate the changes of platelet endothelial cell adhesion molecule-1 (PECAM-1) expression on polymorphonuclear leukocytes (PMNs) in peripheral circulation and pancreatic microcirculation in cerulein-induced acute edematous pancreatitis (AEP). METHODS: Fifty Wistar rats were randomly divided into control group (n = 10) and AEP group (n = 40). A model of AEP was established by subcutaneous injection of cerulein 5.5 and 7.5 μg/kg at 0 and 1 h after the beginning of experiment respectively. PECAM-1 expression on PMNs from splenic vein and inferior vena cava was determined by RT-PCR at mRNA level and determined by flow cytometry at protein level. RESULTS: In experimental rats, an increased PECAM-1 mRNA expression was seen from 4 to 8 h of AEP in peripheral circulation (0.77±0.25%, 0.76±0.28%, 0.89±0.30%, 1.00±0.21%), while in pancreatic microcirculation, expression decreased from 2 h and reached the lowest level at 6 h of AEP (0.78±0.29%, 0.75±0.26%, 0.62±0.28%, 0.66±0.20%). There were significant differences at 8-h time point of AEP between peripheral circulation and pancreatic microcirculation (1.00±0.21% vs 0.66±0.20%, P<0.05). Meanwhile, the difference at protein level was also found. CONCLUSION: A reverse expression of PECAM-1 on PMNs was found between peripheral circulation and pancreatic microcirculation, suggesting that inhibition of PECAM-1 expression may improve the pathological change of AEP.